Sentence Structure and Meaning in Fast-Food Restaurant Tagline: Syntax and Semantic Studies - Ema Halimah; Hendar Hendar (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
Tagline is one of the essential elements in building perception consumers, and it is basically formed in short phrases that provide a description or information from a brand. Linguistics stand as the medium to comprehend the function and the structure of phrases involved in tagline. This research put five data to be analyzed; it consists of five different taglines taken from various tagline of fast-food restaurants. The result showed that from those data analyzed, there are three types of phrases; noun phrase, verb phrase and combination of noun-verb phrases. In terms of providing research data, the qualitative method is used with basic and advanced techniques. The results of this study indicate that the use of the noun phrase, noun phrase and combination phrase. This is indicated by the diversity of the construction of the formation of verbal phrases and noun phrase. The taglines have contributed to the strength of a brand itself. First, the taglines help the restaurants increase awareness. Second, the tagline strengthens the positioning strategy of the brand. The taglines are also using the simple and easy sentence, so they represent the part that essential to the restaurants. Effectiveness of taglines in the fast-food restaurants increase the consumers interest to the product offered by the restaurants.